High incidence of HPV infection in minors with oral squamous cell carcinoma - Ningxiang Wu; Yonghui Li; Xiaokun Ma; Zhen Huang; Zhuoxuan Chen; Weihua Chen; Ran Zhang (BMC, 2024)
Abstract Background Oral squamous cell carcinoma in minors is considered to be a distinct entity from OSCC in older patients, with an uncertain etiology. Human papillomavirus (HPV) infection may trigger the initiation and promote the progression of OSCC, but these roles have not been firmly established.We aimed to explore the correlation between HPV infection and the development of oral squamous cell carcinoma in minors and know the characteristics of OSCC in young patients more thoroughly. Method From January 2013 to December 2022,6 cases of OSCC aged < 15 years were selected from the Department of Oral Pathology, Peking University School of Stomatology, Beijing, China. All cases underwent testing for high-risk HPV mRNA infection using the RNA scope technique, and immunohistochemical staining was performed to investigate the expression of p16, pan-cytokeratin (CK), CK5/6, CK7, CK8/18, epidermal growth factor receptor (EGFR), p53, and Ki-67. Furthermore, we reviewed the literature on OSCC in patients aged < 21 years. Conclusions Minors OSCC is associated with HPV infection, and that p16 can serve as an immunohistochemical marker of HPV positivity.